2018
DOI: 10.1101/360743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmentally-induced epigenetic conversion of a piRNA cluster

Abstract: Transposable element (TE) activity is repressed in animal gonads by PIWI-interacting RNAs (piRNAs), a class of small RNAs produced by specific loci made of TEs insertions and fragments. Current models propose that these loci are functionally defined by the maternal inheritance of piRNAs produced during the previous generation, raising the question of their first activation in the absence of piRNAs. Taking advantage of an inactive cluster of P-element derived transgene insertions, we show here that raising flie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Several studies demonstrate the critical role of cytoplasmic piRNA inheritance from the mother to the progeny in initiating piRNA production (Casier et al, 2019;de Vanssay et al, 2012;Le Thomas et al, 2014b). Together these findings suggest that piRNA biogenesis is governed by a trans-generational feed-forward loop in which piRNA biogenesis is promoted by RDC complex, which in turn is deposited on chromatin guided by cytoplasmically inherited piRNAs.…”
Section:  2023mentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies demonstrate the critical role of cytoplasmic piRNA inheritance from the mother to the progeny in initiating piRNA production (Casier et al, 2019;de Vanssay et al, 2012;Le Thomas et al, 2014b). Together these findings suggest that piRNA biogenesis is governed by a trans-generational feed-forward loop in which piRNA biogenesis is promoted by RDC complex, which in turn is deposited on chromatin guided by cytoplasmically inherited piRNAs.…”
Section:  2023mentioning
confidence: 97%
“…Consistent with siRNAs being dispensable for maintenance of piRNA biogenesis, a previous study showed that the siRNAs are not required for the activity of an artificial piRNA cluster (T1/BX2) (de Vanssay et al, 2012) . On the other hand, increase in the level of antisense transcripts was proposed to be linked to spontaneous activation of BX2 (Casier et al, 2019), suggesting a general role of antisense RNA (and hence the siRNA pathway) in activation of piRNA clusters. Overall, our results and the previous findings suggest a two-step model of cluster activation (Fig.…”
Section: Maternal Sirna Triggers Activation Of Pirna Cluster In the P...mentioning
confidence: 99%